PERBANDINGAN HARGA SAHAM SEBELUM DAN SESUDAH AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hariyanti Hariyanti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The expected objective of this research is To analyze stock return before and after acquisition, the method used in this study using two different test average. The results of this study there are differences in stock returns before and after the acquisition, this is evident after the acquisition, stock prices have increased and significantly influence the performance of the company. Thus the hypothesis is accepted.